'You're only falling into water!': exploring surfers' understandings of concussion in Canadian surf culture. Issue 4 (7th August 2020) - Dean, Nikolaus A; Bundon, Andrea
ABSTRACT: Over the last decade, a growing body of research has explored the linkages between sport and sport-related concussion (SRC). However, collectively, these studies have primarily focused on three commonalities: team sport, contact sport and mainstream sport, all the while ignoring the participants of individualised, non-contact, alternative sports such as surfing. Noting this gap within the existing literature, this qualitative, interview-driven study critically explored how twelve ( n = 12), experienced surfers from the West Coast of Canada came to perceive, give meaning towards and manage sport-related concussion within the ethos of Canadian surfing subculture. The findings demonstrated that surfers expressed mixed and ambiguous understandings of and attitudes towards sport-related concussion. These, we argued, fuelled their headstrong attitudes and embodiments towards sport-related concussion. In addition, the findings revealed that both male and female surfers were willing to push through their concussive injuries as a way of showing one's commitment to the surfing subculture and found that surfers would return-to-surf following an SRC for three primary reasons 1) the wave conditions, 2) limited amount of time to surf and 3) pressures from others in the water. The findings from this study have the potential to inform surfers, surf instructors and surf organisations about the topic of sport-related concussion in surfing and importantly about the topic of head-related safety in surfing.